Evaluation of the thermal processing of meat products in cylindrical cans using the General and Computer methods - GOVARIS (Α. ΓΚΟΒΑΡΗΣ), A.; AMBROSIADIS (Ι. ΑΜΒΡΟΣΙΑΔΗΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2018)
Cylindrical cans (73x109 mm) were filled with luncheon meat and corned beef were sterilized with steam at 121.1°C for 96 and 91 min, respectively. The evaluation of the thermal processing was made using the General method and a Computer method. The General method used the experimental temperatures recorded by thermocouples while the Computer method predicted the internal temperatures of foods in cylindrical cans, using the finite difference numerical solution of heat conduction equation. By the end of heating at 121.1 °C and following cooling, comparison of the (Fo) value and the decimal reduction (log D121.1) of the initial population of the Clostridium botulinum at the geometric centre of the can for both examined meat products, estimated by the General method with those estimated by the Computer method, showed that there was no any significant difference between them (P>0.05). Comparison of recorded temperatures at the geometric centre of cans of both meat products with those estimated by the Computer method showed that, there was no any significant difference between them (P>0.05) during heating at 121.1 ° C, but a significant difference between them (P<0.05) was observed by the end of cooling.